(untitled) (Educação e Pesquisa, 2023)
The practice among students of sharing photos that expose the nudity of girls has been experienced in most educational institutions in Brazil and around the world. Several cases reported in the media portray situations of humiliation and persecution that may lead, in addition to psychological damage, to problems in social relationships, lowering performance, school dropout and even suicide. The aim of this work was to discuss the relationships that have been established at school in the face of the practice of sharing naked self-portraits and the unauthorized dissemination of intimate images of girls. Twenty-seven in-depth interviews were carried out with girls and women from different Brazilian regions who had their intimacy exposed at different times in their lives, in addition to health and social care professionals who assisted adolescents and adult women who went through this situation. The data pointed to practices of negligence in relation to situations of violence, blaming girls and unpreparedness to guide questions concerning the experience of sexuality in a pleasant and healthy way. It was observed that these new practices of sexuality and violence against girls have resumed, in institutions, the opposition between manifestation of sexuality and good school performance. It argues for an education in sexuality based on the issue of desire.